Peran Keimigrasian terhadap Penyalagunaan Izin Tinggal Warga Negara Asing di Kota Medan Pada Masa Pandemi Covid-19 - Rumagit, Joni; Isnaini, Isnaini; Ramadhan, M. Citra (Mahesa Research Center, 2022)
This thesis research uses normative legal research, namely research that refers to the legal norms contained in the laws and regulations that apply as a normative footing. Immigration law regulations regarding residence permits for foreign citizens (WNA) in Indonesia during the Covid-19 pandemic: the 1945 Constitution of the Republic of Indonesia, Law of the Republic of Indonesia Number 6 of 2011 concerning Immigration, Government Regulation of the Republic of Indonesia Number 31 of 2013 concerning Guidelines for the Implementation of Law Number 6 of 2011 concerning Immigration. The role of the Immigration Office Special Class I TPI Medan in supervising the residence permit of foreign citizens (WNA) in Medan City during the Covid-19 pandemic: a. The Role of Immigration as a Structural Component, b. The Role of Immigration Oversight of Foreign Citizens (WNA) Stay Permits in Medan City During the Covid-19 Pandemic, c. The Role of Immigration as a Substance Component. d. The Role of Immigration as a Component of Culture or Legal Culture.